The Effect of Chewing Simulation on Flexural Strength of Different Lithium Disilicate Ceramics - Alsulimani O; Yousief SA; Al-Dabbagh RA; Attar EA; Bukhary DM; Algamaiah H; Musawa K; Subahi A; Abuzinadah SH; Alhaddad AJ; Alqahtani WMS; Emam ANM; et al. (Clinical, Cosmetic and Investigational Dentistry)
Osamah Alsulimani,1 Salah A Yousief,2,3 Raghad A Al-Dabbagh,4 Esraa A Attar,4 Dalea M Bukhary,4 Hamad Algamaiah,5 Khadija Musawa,6 Awatif Subahi,6 Samar H Abuzinadah,7 Abdulrahman J Alhaddad,4 Waleed MS Alqahtani,8 Abdel Naser M Emam,9 Mohammad A Alqhtani,9 Ahmed M Elmarakby2,10 1Department of Oral Diagnostic Sciences, Faculty of Dentistry, King Abdulaziz University, Jeddah, Saudi Arabia; 2Department of Restorative and Prosthetic Dental Sciences, College of Dentistry, Dar Al Uloom University, Riyadh, 13313, Saudi Arabia; 3Department of Crown and Bridge, Faculty of Dental Medicine, Al-Azhar University, Assuit, Egypt; 4Department of Oral and Maxillofacial Prosthodontics, Faculty of Dentistry, King Abdulaziz University, Jeddah, Saudi Arabia; 5Department of Restorative Dental Science, King Saud University, College of Dentistry, Riyadh, Saudi Arabia; 6BDS, General Dentist, Faculty of Dentistry, King Abdulaziz University, Jeddah, Saudi Arabia; 7Department of Restorative Dentistry, Faculty of Dentistry, King Abdulaziz University, Jeddah, Saudi Arabia; 8Department of Prosthetic Dentistry, College of Dentistry, King Khalid University, Abha, Saudi Arabia; 9Department of Prosthetic Dental Science, Faculty of Dentistry, Najran University, Najran, Saudi Arabia; 10Department of Operative Dentistry, Faculty of Dental Medicine, Al-Azhar University, Assuit, EgyptCorrespondence: Salah A Yousief, Department of Restorative and Prosthetic Dental Sciences, College of Dentistry, Dar Al Uloom University, Riyadh, 13313, Saudi Arabia, Tel +966598045800, Email Salah.a@dau.edu.saBackground: Improved Lithium Disilicate Ceramic has been highly valued in dentistry for over two decades, owing to its durability and aesthetic qualities, making it a preferred choice for both anterior and posterior crowns.Objective: This study aimed to evaluate the flexural strength of two types of lithium disilicate blocks post-chewing simulation.Materials and Methods: Seventy-six lithium disilicate specimens were utilized in this study. They were divided into two primary groups (n=38) based on two brands: IPS Emax CAD LT (Ivoclar Vivadent) designated as (E), and Initial Lisi LT/B1 (GC America) designated as (L). Each primary group was further split into two subgroups (n=19) based on surface treatment: group E into (E0 & E1) and group L into (L0 & L1). Half of the specimens were subjected to flexural testing without chewing simulation cycles and designated as (E0 and L0), while the remainder were tested after 24× 104 cycles of chewing simulation and designated as (E1 and L1). The ceramic surfaces were examined using SEM before and after loading.Statistical Analysis: Data were gathered, organized, and subjected to Shapiro–Wilk’s and Levene’s tests (p-value < 0.05), followed by analysis with Brown-Forsythe two-way ANOVA and Tamhane’s post hoc tests to assess group differences (p-value < 0.05).Results: There were significant statistical differences in the flexural strength values between the different brand groups before and after chewing simulation (p-value < 0.05). The IPS Emax CAD group showed values approximately twice that of the Initial Lisi group (307.2– 310.5 MPa ± 48.5– 67 vs 148.1– 158.5 MPa ± 24.6– 25.6).Conclusion: Within the limitation of the current study, the following may be concluded: 1. The study’s findings suggest that Initial Lisi blocks should not be used for posterior teeth restorations. 2. This study can provide valuable insights for dental professionals to make informed decisions about which material is most appropriate for various clinical situations.Keywords: lithium disilicate, flexural strength, ceramics, mastication